2000
DOI: 10.1021/jm001000c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of a Novel, Highly Potent Progesterone Receptor Antagonist

Abstract: Herein we describe the chemical synthesis and pharmacological characterization of a novel, highly potent progesterone receptor (PR) antagonist, ZK 230211. The introduction of a 17alpha-pentafluorethyl side chain in the D-ring of the steroid skeleton allowed the combination of high antiprogestagenic activity with little or no other endocrinological effects. In contrast to many other antiprogestins, ZK 230211 did not convert to an agonist in the presence of protein kinase A (PKA) activators and showed high antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 31 publications
2
63
0
Order By: Relevance
“…This discrepancy suggested the possibly important role of iNOS in the development of chorionic villi during early gestation. In rodents, Saxena et al reported up-regulation of iNOS in implantation site [46] and Fuhrmann et al demonstrated the importance of the combination of iNOS and progesterone in implantation [47]. By contrast, Ariel et al identified eNOS immunoreactiviry in the human extravillous trophoblastic cells, suggesting the possible involvement of eNOS in human implantation [48].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy suggested the possibly important role of iNOS in the development of chorionic villi during early gestation. In rodents, Saxena et al reported up-regulation of iNOS in implantation site [46] and Fuhrmann et al demonstrated the importance of the combination of iNOS and progesterone in implantation [47]. By contrast, Ariel et al identified eNOS immunoreactiviry in the human extravillous trophoblastic cells, suggesting the possible involvement of eNOS in human implantation [48].…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that the functions of progesterone and RU486 can be differentially mediated by two PR isoforms that arise from the same gene and function to exhibit different transcription regulatory activities in vitro and in vivo (Conneely et al, 2001;Fuhrmann et al, 2000). In the presence of cAMP, RU486 can exhibit inappropriate gene activation in T47D subline expressing PR isoform B but not in cells expressing isoform A (Sartovius et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…mice so far (Banaszak et al, 2000;Fuhrmann et al, 2000;Sanchez-Criado et al, 2000;Xu et al, 2000;Slayden et al, 2001) . We selected two doses of ZK (6 and 9 mg/kg) based on previous studies in rats (Xu et al, 2000;Sanchez-Craido et al, 2000).…”
Section: Determine Whether Zk Blocks Lordosis Behavior and Y1r Expresmentioning
confidence: 95%
“…neonatally (P0-P10) for the males and prepubertally (P15-P25) for the females. RU486 has been criticized for its use as selective PR antagonist since it is known to interfere with glucocorticoid receptors, which is not the case for ZK137316 (Banaszak et al, 2000;Fuhrmann et al, 2000;Sanchez-Criado et al, 2000;Xu et al, 2000;Slayden et al, 2001). …”
Section: Accepted M Manuscriptmentioning
confidence: 99%